DEVELOPING THE METHODS OF FOOD PRESERVATIVES EXTRACTION FROM COMPLEX MATRICES FOR BIOASSAY PURPOSE - A. V. Samoilov; N. M. Suraeva; S. V. Koptsev; S. V. Glazkov (Пищевые системы)
The presence of food additives in food products may be associated with the risk of their toxic effects on human body. Therefore, the study of approaches to testing their safety seems to be a particularly urgent task. The aim of this study was to determine the conditions for extracting food preservatives from the samples of preserved pureed vegetables for further bioassay of the extract obtained in the Allium test. Onion roots were used as a test object in this method. Two extraction methods of benzoic and sorbic acids added to pureed vegetables have been developed. Distilled water and acetone were used as extracting solutions. The extraction efficiency was evaluated on Shimadzu Prominence LC-20 liquid chromatograph (Japan) in the ultraviolet range, wavelength 235 nm (benzoic acid), 285 nm (sorbic acid). According to the results of studies using both water and acetone as extractants, the degree of preservatives extraction was approximately the same and quite high. In the quantitative calculation of the preservatives content in pureed vegetables, the value of the correction factor was 0.8. However, due to certain production characteristics of this product, i. e. the stage of cauliflower homogenization, obtaining an extract with acetone seems to be more acceptable for the Allium test conditions.